2016
DOI: 10.21037/jtd.2016.12.77
|View full text |Cite
|
Sign up to set email alerts
|

The application of thromboelastogram in detection of indexes of antiplatelet therapy for coronary heart disease

Abstract: Background: This study aims to explore the application value of thromboelastogram (TEG) in antiplatelet therapy in coronary artery intervention.Methods: A retrospective analysis of 90 cases of coronary interventional treatment was conducted in our hospital from January 2010 to January 2012. Cases were divided into three groups, according to the kind of coronary heart disease: angina pectoris (AP) group (30 cases), unstable angina pectoris (UAP) group (30 cases) and acute myocardial infarction (AMI) group (30 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In the research of Pandey et al [ 23 ], the prediction ability of TEG on bleeding after central venous catheter insertion in patients with liver cirrhosis was explored, and it was found that the AUC of K value in predicting bleeding of patients was 0.694, and that of MA in predicting bleeding-free AUC was 0.719, which was sensitive to coagulopathy. This also indicated that monitoring these patients by TEG can prepare for antiplatelet or antithrombotic therapy in time once the patients are found to be in a high coagulation state, and the blood transfusion scheme can be improved by predicting the bleeding situation of patients during operation [ 24 ]. At the end of the study, we also analyzed the risk factors of LEDVT in patients with cerebral infarction through the logistics regression equation and found that FIB, angle, and MA values were the risk factors of patients while R and K values were the protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the research of Pandey et al [ 23 ], the prediction ability of TEG on bleeding after central venous catheter insertion in patients with liver cirrhosis was explored, and it was found that the AUC of K value in predicting bleeding of patients was 0.694, and that of MA in predicting bleeding-free AUC was 0.719, which was sensitive to coagulopathy. This also indicated that monitoring these patients by TEG can prepare for antiplatelet or antithrombotic therapy in time once the patients are found to be in a high coagulation state, and the blood transfusion scheme can be improved by predicting the bleeding situation of patients during operation [ 24 ]. At the end of the study, we also analyzed the risk factors of LEDVT in patients with cerebral infarction through the logistics regression equation and found that FIB, angle, and MA values were the risk factors of patients while R and K values were the protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboelastography (TEG) is a new type of detection method that can evaluate the whole process of platelet aggregation in the blood [24, 25]. It has the following advantages over LTA.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this examination can be used to predict the bleeding situation, hypercoagulation, and fibrinolysis. In patients undergoing antiplatelet therapy, the examination of platelet function with TEG is useful for monitoring antiplatelet therapy's effectiveness and determining the choice of antiplatelet drugs to be given to each patient (Swallow et al, 2006;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%